The New Covenant - Jeremiah 31:30-33 (31:31-34) in Jewish Interpretation - Goshen-Gottstein, Alon (Studies in Christian-Jewish Relations, 2020)
Jeremiah 31:30-33 is the famous oracle of a future new covenant. This text is foundational for Christianity. However, other than polemical uses in the middle ages it has almost no echo in classical Jewish sources. The reason is not because of its significance for Christianity, but due to the decline in the conceptual centrality of the notion of "covenant" and due to the fact that other than suggesting some future change, it has little present significance. After reviewing classical uses, this article surveys later developments in Jewish spiritual literature, especially Hassidic literature. In this literature the term "new covenant” receives new life. This is made possible due to the individualization of the covenant and the dissociation of the term from the complex of ideas in Jeremiah. Covenant becomes a way of affirming commitment, reestablishing a personal relationship with God, and even receiving inspiration from God. In the thought of some Hassidic authors it also plays an important role in a view of history, once it is seen as part of an ongoing historical movement that is relevant to the present, and not only as a future oriented prophecy. These later developments provide new and interesting points of contact between Jewish and Christian uses and invite us to consider the ongoing vitality and relevance of the oracle in Jeremiah.